Evaluation of the complementary feeding practices, dietary intake, and nutritional status of infants on a cow's milk protein elimination diet - Juliana Frizzo; Vanessa C.C. Rodrigues; Patrícia G.L. Speridião; Mauro B. Morais (Elsevier, 2022)
Objective: To evaluate the complementary feeding practices, food intake, and nutritional status of infants on a cow's milk protein elimination diet. Methods: A cross-sectional and observational study was conducted to compare infants aged 4-18 months who were on a cow's milk protein elimination diet with a control group of healthy infants without any dietary restrictions. General information on the child's health, demographic data, and food consumption were collected. Results: The study included 96 infants in the elimination diet group and 99 in the control group. In the elimination diet group, the median age (in months) of introduction of solid foods (5.0 × 4.0; p < 0.001) and water (5.5 × 4.0; p < 0.05) was later, consumption of soft drinks and industrialized cookies was less frequent (p < 0.05), and a lower index of complementary feeding inadequacies (2.75 × 3.50; p < 0.001) was observed. The elimination diet group presented lower individual values of Z scores for weight/age, weight/height, and body mass index/age, although they were fed with higher amounts of energy (117.4 × 81.3 kcal/kg of weight; p < 0.001) and macro-and micronutrients, except for vitamin A. In the elimination diet group, breast milk and its substitutes contributed to more than 67% of energy intake. Although calcium consumption was a deficit in 31.5% of the infants, none received supplementation. Conclusion: Infants on an elimination diet presented more adequate complementary feeding practices and higher nutritional intake, despite lower body weight values.